UPAYA PEMBERDAYAAN SARANA PADA PEMBELAJARAN SENI MUSIK DI SMP NEGERI 15 PADANG - Mulia Rahmat Sitorus; Yensharti Yensharti; Yos Sudarman (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to explain the efforts of empowering learning facilities in the learning of music arts at SMP Negeri15 Padang. The type of this research was qualitative research with a descriptive analysis approach. The object of research was school, teachers, and students who were involved randomly, that were some students who were practicing extracurricular self-development of music and students who were studying arts and culture (music) at SMP Negeri 15 Padang in the even semester of 2017/2018 school year. Research instruments were data documentation, observation and interviews. The results showed that even though most of the students attending SMP Negeri 15 Padang were underprivileged students, there was no funding specifically in the provision of musical learning facilities at school, the achievement and quality of self-development activities and the learning of music at SMP Negeri 15 Padang 15 yet could be maintained. Apparently, there was a strategy in terms of empowering learning facilities that support extra and intra-curricular activities which caused students to have a disciplined attitude and responsibility in using musical instruments for both types of activities. Keywords: Empowerment, Learning Facilities, Learning Music Arts